"أهمية استعمال تكنولوجيات المعلومات والاتصال في خلق الزبائن في القطاع السياحي في الجزائر -دراسة حالة مركب الغزال الذهبي بولاية الوادي-" - فراجي, أميرة; لويزة, يوسف (University of eloued جامعة الوادي, 2020)
" في هذا البحث حاولنا دراسة أهمية استعمال تكنولوجيات المعلومات والاتصال في خلق الزبائن في القطاع السياحي وذلك من خلال : - التعريف بالسياحة وانواعها واهميتها ومدى مساهمتها في زيادة اقتصاد الدولة؛ - حاولنا التعرف على تكنولوجيا المعلومات والاتصال والتطور التاريخي لها وكيف ساهمت في تطور السياحة وساعدت المؤسسات على اعطاء صورة صحيحة على مستوى الخدمات . و للإجابة عن اشكالية البحث(إلى أي مدى تكمن أهمية استعمال بعض تكنولوجيات المعلومات والاتصال في خلق زبائن جدد وتطوير الحصة السوقية السياحية في الجزائر؟) ،قمنا بدراسة ميدانية للمركب الغزال الذهبي في ولاية الوادي .وذلك من خلال اعداد استبيان يتكون من 3محاور للإجابة على التساؤلات الفرعية ،تمت الدراسة على عينة ضمت(30) عامل من جميع أصناف عمال المؤسسة محل الدراسة، وتمت معالجة البيانات من خلال برنامجEXCEL)) ونظام (SPSS): ومن خلال الدراسة توصلنا الى النتائج التالية: - يوجد استعمال لتكنولوجيات المعلومات والاتصال في المؤسسة السياحية؛ - تستثمر المؤسسة بصورة دائمة احدث تكنولوجيات المعلومات والاتصال المتعلقة بالقطاع السياحي؛ - زيادة الطلب من طرف الزبائن عن طريق استعمال تكنولوجيات المعلومات و الاتصال في المؤسسة؛ - لا يوجد عراقيل التي تتعلق بنقص الاستثمار في بعض تكنولوجيات المعلومات و الاتصال المتعلقة بالمؤسسة السياحية. من خلال الدراسات السابقة نقترح بعض التوصيات : مع كل هذا التطور تبقى لدينا بعض النقائص التي تستوجب الاهتمام في هذا القطاع ولذلك اقترحنا بعض التوصيات ندكر منها: - تطوير خدمات الاتصال من خلال شبكة انترنت ذات تدفق عالي جدا ؛ - تطوير تطبيق الكتروني للهواتف الذكية خاص بالمركب لأجل تسهيل التواصل مع الزبائن، الضيوف وحتى لاستقطاب زبائن جدد من خلال تسهيل عملية الحجز وعرض الخدمات. - تعزيز نظام أمني يعتمد على تكنولوجيات المعلومات والاتصال يسهل عملية أخذ معلومات الزبائن وحفظها في قاعدة البيانات لتسريع عملية الاستقبال و تحسينها ؛ - وضع نظام خاص بالزبائن الاوفياء يمكنهم من الاطلاع على برامج المركب وخاصة العروض التحفيزية والمناسبات""In this research, we tried to study the importance of using information and communication technologies in creating customers in the tourism sector, through: Introducing tourism, its types, importance and the extent of its contribution to increasing the country's economy; - We tried to get acquainted with information and communication technology and its historical development and how it contributed to the development of tourism and helped institutions to give a correct image on the level of services. In order to answer the problem of the research (to what extent is the importance of using some information and communication technologies in creating new customers and developing the tourism market share in Algeria?), we conducted a field study of the Golden Ghazal compound in the state of El-Oued, by preparing a questionnaire consisting of 3 axes to answer the questions The study was conducted on a sample of (30) workers from all types of workers in the institution under study, and the data was processed through the EXCEL program and the (SPSS) system: through the study, we reached the following results: - There is a use of information and communication technologies in the tourist establishment; - The Foundation constantly invests in the latest information and communication technologies related to the tourism sector; - Increasing demand from customers through the use of information and communication technologies in the enterprise; - There are no obstacles related to the lack of investment in some information and communication technologies related to the tourism establishment. Through previous studies, we suggest some recommendations: With all this development, we still have some shortcomings that require attention in this sector. Therefore, we proposed some recommendations, including: - development of communication services through a very high-speed Internet; - Developing an electronic application for smart phones for the boat in order to facilitate communication with customers, guests, and even to attract new customers by facilitating the reservation process and offering services. - Strengthening a security system based on information and communication technologies that facilitates the process of taking customer information and saving it in the database to speed up and improve the reception process; - Establishing a special system for loyal customers, enabling them to view the boat's programs, especially the incentive offers and events."
مذكرة ماستر ادارة اعمال
Keywords: تكنولوجيات المعلومات و الاتصال؛ الزبائن؛ القطاع السياحي; information and communication technologies; customers; tourism sector